Risk stratification of newly diagnosed multiple myeloma patients - Ara Islam, Ismat; Samarat, Mohsin Hasan; Mahzabin, Nishat; Jahan, Nusrat; Akhlak-Ul-Islam, M.; Shah, M. Salahuddin; Poddar, Sharup Chandra; Reza Kabir, M. Maruf; Nasrin, Papri; Rahman, M. Aminur; Akhter, Nasrin; Afroz Chowdhury, Nowreen; et al. (International Journal of Research in Medical Sciences, 2024)
Background: Multiple Myeloma is a neoplastic proliferation of plasma cells, associated with an M (monoclonal) protein in serum and/or urine and evidence of organ damage. Despite advances in treatment, the disease remains heterogeneous, necessitating a comprehensive understanding of its risk stratification. Risk-adapted initial therapy, maintenance therapy, refractory disease management and prognosis varies according to risk group. The aim of our study is to categorize the newly diagnosed MM patients according to their risk groups. Methods: This cross-sectional observational study was conducted at the Department of Haematology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from August 2019 to July 2020. A total of 31 newly diagnosed MM patients were enrolled based on specific inclusion and exclusion criteria. Risk stratification was performed using ISS, R-ISS, mSMART criteria and Avets risk group categorization. Result: The majority of the patients were male (64.52%) and aged between 55-64 years (45.16%). Clinical features predominantly included low back pain (74.19%) and general weakness (38.71%). Cytogenetic abnormalities were noted in 38.7% of the patients, with del (13q) being the most common (32.30%). Most patients were in ISS Stage III (70.97%) and R-ISS Stage II (48.39%). According to mSMART criteria, 80.65% were at standard risk while Avet's risk stratification identifies 58.06% were at intermediate risk. Conclusion: The study reveals a high prevalence of patients in advanced ISS stages and intermediate to high-risk categories, emphasizing the need for early and personalized intervention strategies.